Crop Performance and Weed Suppression by Weed-Suppressive Rice Cultivars in Furrow- and Flood-Irrigated Systems under Reduced Herbicide Inputs. Issue 2 (June 2014) - Gealy, David R.; Anders, Merle; Watkins, Bradley; Duke, Sara
Abstract : Weed control in rice is challenging, particularly in light of increased resistance to herbicides in weed populations and diminishing availability of irrigation water. Certain indica rice cultivars can produce high yields and suppress weeds in conventional flood-irrigated, drill-seeded systems in the southern United States under reduced herbicide inputs, but their response to reduced irrigation inputs in these systems in not known. Rice productivity and weed control by weed-suppressive cultivars and conventional nonsuppressive cultivars were evaluated in a nonflooded furrow-irrigated (FU) system and a conventionally flooded (FL) system under three levels of weed management (herbicide inputs) in a 3-yr field study. Rice yields across all weed management levels yielded ∼ 76% less in the FU system than in the FL system. The allelopathic indica cultivar, 'PI 312777', and commercial hybrid rice 'CLXL729' generally produced the highest grain yields and greatest suppression of barnyardgrass in both irrigation systems. 'Bengal' and 'Wells' were the top-yielding conventional cultivars whereas 'Lemont' and 'CL171AR' yielded the least. Weed suppression by PI 312777 and CLXL729 under "medium" weed management was equivalent to that of Lemont and CL171AR at the "high" management level, suggesting that the weed-suppressive cultivars may be able to compensate for suboptimal herbicide inputs or incomplete weed control.